2021
DOI: 10.1371/journal.pone.0246012
|View full text |Cite
|
Sign up to set email alerts
|

Assessing biomass and primary production of microphytobenthos in depositional coastal systems using spectral information

Abstract: In depositional intertidal coastal systems, primary production is dominated by benthic microalgae (microphytobenthos) inhabiting the mudflats. This benthic productivity is supporting secondary production and supplying important services to humans including food provisioning. Increased frequencies of extreme events in weather (such as heatwaves, storm surges and cloudbursts) are expected to strongly impact the spatiotemporal dynamics of the microphytobenthos and subsequently their contribution to coastal food w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 83 publications
1
6
0
Order By: Relevance
“…The significant increase in MPB biomass with elevation in the tidal flats matched the findings of previous studies of other European tidal flats (Brotas et al, 1995;van der Wal et al, 2010;Daggers et al, 2020). Upper tidal flats fall dry for a longer period of time during low tide, resulting in higher stability (low resuspension rate) of the sediment, and longer exposure to sunlight, which therefore increases the photosynthetic period (van der Wal et al, 2017;Jacobs et al, 2021). We did not find a significant relationship between ENS and elevation, which is in contrast to previous studies that observed a decrease in MPB diversity with increasing elevation, driven by local in-situ factors, such as sediment grain size and mud content (Scholz and Liebezeit, 2012b;Ribeiro et al, 2021).…”
Section: Elevation Mpb Biomass and Pigment Diversity Patterns On Natu...supporting
confidence: 86%
See 3 more Smart Citations
“…The significant increase in MPB biomass with elevation in the tidal flats matched the findings of previous studies of other European tidal flats (Brotas et al, 1995;van der Wal et al, 2010;Daggers et al, 2020). Upper tidal flats fall dry for a longer period of time during low tide, resulting in higher stability (low resuspension rate) of the sediment, and longer exposure to sunlight, which therefore increases the photosynthetic period (van der Wal et al, 2017;Jacobs et al, 2021). We did not find a significant relationship between ENS and elevation, which is in contrast to previous studies that observed a decrease in MPB diversity with increasing elevation, driven by local in-situ factors, such as sediment grain size and mud content (Scholz and Liebezeit, 2012b;Ribeiro et al, 2021).…”
Section: Elevation Mpb Biomass and Pigment Diversity Patterns On Natu...supporting
confidence: 86%
“…We did not find a significant relationship between ENS and elevation, which is in contrast to previous studies that observed a decrease in MPB diversity with increasing elevation, driven by local in-situ factors, such as sediment grain size and mud content (Scholz and Liebezeit, 2012b;Ribeiro et al, 2021). Other studies related the opposite pattern (increasing diversity with elevation) to stronger wave action and hydrodynamic conditions at the seaward side of the elevation gradient, potentially causing resuspension of MPB, and the mixing of sediments and thus burying MPB cells into deeper sediment layers (Underwood and Kromkamp, 1999;van der Wal et al, 2010;Jacobs et al, 2021). Janousek (2009) also reported higher pigment diversity in the salt marsh compared to the adjacent bare tidal flats, due to the various conditions provided by salt marsh vegetation already described earlier.…”
Section: Elevation Mpb Biomass and Pigment Diversity Patterns On Natu...mentioning
confidence: 99%
See 2 more Smart Citations
“…Diatoms can break down and recycle environmental nutrients, such as nitrogen, which is necessary in typically nitrogen-limited marine environments [8,9]. Diatoms are also very important autotrophs, acting as major primary producers in marine environments [10,11].…”
Section: Introductionmentioning
confidence: 99%